The Exceptional Persistence of India's Unorganized Sector - Ghani, Ejaz; Kerr, William R.; O'Connell, Stephen D. (World Bank, Washington, DC, 2013)
The transformation of India's unorganized sector is important to its modernization, growth, and attainment of regional economic equality. This paper documents several key facts about India's unorganized sector in manufacturing and services. First, the unorganized sector is large, accounting for more than 99 percent of establishments and 80 percent of employment in manufacturing. Second, the unorganized sector is stubbornly persistent -- it accounted for 81 percent of manufacturing employment in 1989 and 2005. Third, this persistence is not due to particular subsets of industries or states, as most industries and states show limited change in unorganized sector employment shares. Fourth, the degree to which localized unorganized activity exists is important as it is associated with weaker production functions for manufacturing firms. Building from these facts, the paper investigates conditions promoting transformation by state-industry. Decomposition exercises find that both within and between adjustments for state-industries weakly reduce unorganized sector shares. The aggregate persistence instead comes from the covariance term, where fast-growing state-industries witness rising unorganized sector activity. Regressions quantify that growth in the organized sector by state-industry reduces the unorganized sector employment share, but only marginally reduces employment levels in unorganized activity. Analysis of the establishment size distribution highlights that entrepreneurship and larger organized sector plants are most important for transitions in the manufacturing sector, while small establishments play a key role in the services sector.